Alternatives to University Education in Germany - Kehm, Barbara (International Higher Education, 2021)
The German higher education system is a binary system consisting predominantly of universities and universities of applied sciences (UASs), originally conceived as teaching-only institutions offering applied degrees. This article focuses on the UAS sector, but also provides information on vocational education and training (regarded as postsecondary, but nonacademic and not part of higher education). It shows why and how an increasing blurring of boundaries is taking place among the different sectors of postsecondary education.